Efektivitas Teknik Expressive Writing Dalam Menurunkan Burnout Pada Pembelajaran di Sekolah Menengah Atas - Ayu Sri Ginanti; Uli Makmun Hasibuan; Dania; Julia Siregar (Social Science and Contemporary Issues Journal, 2024)
Burnout in the context of learning in high school classes is a condition of physical, emotional and mental exhaustion experienced by teachers or students due to prolonged stress in the school environment. The characteristics of burnout can include excessive tiredness, inability to concentrate, feelings of hopelessness, and a cynical attitude towards work. Expressive writing technique is a cognitive psychotherapy method that can help overcome anxiety, stress and depression. This method allows people to reflect on their thoughts and feelings about unpleasant events, which can be done individually or in groups. This method helps people to control their emotions, gain new energy, relieve their stress, and discern what they feel. Expressive Writing Techniques can help mental health. According to Fikri (2014), expressive writing has several benefits, namely: 1. Increasing a person's understanding of what they say and what they say about other people; 2. Increase creativity, expression and self-esteem; 3. Improve communication and interpersonal skills; 4. Expressing excessive emotions (catharsis), which reduces tension; and 5. Increase a person's ability to adapt and face problems.